The Influence of the Flypaper Effect on Regional Financial Performance with SiLPA as Moderator in South Sulawesi Regencies - Fajriani Azis; M. Ridwan Tikollah; Asmar Yunus; Magfirah Wahyu Ramadhani (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
This study aims to analyze the effect of the flypaper effect on regional financial performance with the budget surplus as a moderating variable in districts/municipalities in South Sulawesi Province. The flypaper effect refers to the phenomenon in which local governments are more responsive to central government transfers, particularly the general allocation fund, than to local own-source revenue. This study employs panel data from 24 districts/municipalities for the period 2021–2023, using a quantitative approach through multiple linear regression and moderated regression analysis based on the interaction model. The results indicate that general allocation fund and local own-source revenue have a significant effect on regional expenditure, while the special allocation fund and revenue sharing fund do not. The flypaper effect is confirmed, with general allocation funds being more “sticky” to regional government spending compared to local own-source revenue. Furthermore, budget surplus significantly moderates this relationship, where high budget surplus tends to weaken, while low budget surplus strengthens the influence of the flypaper effect on regional financial performance. These findings highlight the importance of efficient budget management to ensure that transfer funds optimally enhance regional fiscal performance.